An assessment of the impact of public debts on development in Nigeria (2003-2020) (Journal of Economic Research & Business Administration, 2022)
This study assessed the impact of public debt on development of Nigeria. It specifically investigatedthe relationship between human development index, per capital income, growth rate and public debt inNigeria from 2003 to 2020. This study adopted quantitative research design. Relevant data regarding thevariable’s under-study were extracted from the Debt Management Office (DMO-2020) and UNESCOInstitute of Statistics (2020) while regression model was used to analyze the data. The study revealedamong other things that; there is presence of co-integration (long-run relationship) among the variablesin the model. The t-statistics of -2.297997 with 0.0388 p-value implies negative and significant relationshipexists between foreign debt and human development index, t-statistics of 2.557340 with 0.0239p-values implies positive and significant relationship exists between foreign debt and per capital incomeand also t-statistics of -0.658730 with p-value of 0.5216 implies negative and insignificant relationshipexistence between foreign debt and growth rate. The overall result of the f-statistics of 4.109504 withProb.(F-statistic) of0.029617 shows that all the explanatory variables jointly have significant impact onforeign debt both in the short and long run. The study concluded that there is significant relationshipbetween public debt and development in Nigeria, depending on the variable of interest. Likewise, thestudy recommended among other things that government should ensure efficiency and effectiveness inthe public debt management due to the negative and significant influence of human development indexon development both in the long run and short run, also the negative and insignificant influence offoreign debt on development in Nigeria which is a pure indication of poor public debt management inthe country. Also, the component governments in Nigeria should reduce it public borrowing as it has asignificant inverse effect on the development of the country in the long run.Key words: Public debt, Per capital income, Human Development Index, Growth rate and Development.